2001
DOI: 10.1086/324223
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Burst Phenomenology, Shock Dynamo, and the First Magnetic Fields

Abstract: A relativistic collisionless shock propagating into an unmagnetized medium leaves behind a strong large-scale magnetic field. This seems to follow from two assumptions: (i) GRB afterglows are explained by synchrotron emission of a relativistic shock, (ii) magnetic field can't exist on microscopic scales only, it would decay by phase space mixing. Assumption (i) is generally accepted because of an apparent success of the shock synchrotron phenomenological model of GRB afterglow. Assumption (ii) is confirmed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
155
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(164 citation statements)
references
References 8 publications
7
155
0
Order By: Relevance
“…The generated smallscale field should decay (Gruzinov 2001;Milosavljević & Nakar 2006), so B could be even lower. According to Panaitescu & Kumar (2002) and Yost et al (2003), the observed spectra and light curves of the GRB afterglows imply B $ 10 À3 Y10 À1 in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generated smallscale field should decay (Gruzinov 2001;Milosavljević & Nakar 2006), so B could be even lower. According to Panaitescu & Kumar (2002) and Yost et al (2003), the observed spectra and light curves of the GRB afterglows imply B $ 10 À3 Y10 À1 in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing difficulty with this assumption has been that the inferred magnetic field needed to fit the afterglow data typically requires that the magnetic energy density exceeds by many orders of magnitude the magnetic energy density that would be expected from the shock compression of the interstellar magnetic field of the host galaxy (Gruzinov & Waxman 1999;Gruzinov 2001). Many authors have therefore assumed that the shock somehow manufactures field energy to meet this requirement, but no convincing mechanism has been proposed to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) despite the larger kinetic energy of the protons. Gruzinov (2001) anticipated this when he excluded the case where a small parameter in the theory might be important in his analysis of the Weibel instability: our analysis shows that the relevant small parameter isω 2 pp /Ω 2 ∼ 4m e /3m p . The result is a small equipartition parameter (44).…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, the Weibel instability, which generates purely growing magnetic fields, is triggered by electron temperature anisotropy or by beams of contrastreaming electron streams in plasmas. The importance of the Weibel instability has been recently recognized in the context of the magnetic field generation in cosmological [8][9][10] and laboratory [11] plasmas. Computer simulations [12] conclusively demonstrate the generation of magnetic fields due to colliding electron clouds in an unmagnetized electron-ion plasma.…”
mentioning
confidence: 99%